2004
DOI: 10.1002/cne.20180
|View full text |Cite
|
Sign up to set email alerts
|

Superior olivary contributions to auditory system plasticity: Medial but not lateral olivocochlear neurons are the source of cochleotomy‐induced GAP‐43 expression in the ventral cochlear nucleus

Abstract: A unilateral cochlear lesion induces expression of the growth and plasticity-associated protein 43 (GAP-43) in fibers and their varicosities on specific types of postsynaptic profiles in the ventral cochlear nucleus (VCN), suggesting the induction of synaptic remodeling. One candidate population from which GAP-43 might emerge was neurons of the lateral olivocochlear (LOC) system residing in the lateral superior olive (LSO). Upon cochleotomy, these neurons express GAP-43 mRNA and GAP-43 protein. However, retrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 79 publications
4
61
0
Order By: Relevance
“…The increases of muscarinic receptor binding after cochlear ablation might reflect new expression of muscarinic receptors and might result from sprouting of new fibers, possibly from OCN or from the ventral, trapezoid body, pathway (Bilak et al, 1997;Illing et al, 1997Illing et al, , 2000Kraus and Illing, 2004). Sprouting in some CN regions is supported by our finding of increased ChAT activity after cochlear ablation, but it is not supported in those regions, such as DCN layers, where increases of receptor binding occurred without increases of ChAT activity (Jin et al, 2005).…”
Section: Effects Of Cochlear Ablation On Muscarinic Acetylcholine Recmentioning
confidence: 54%
“…The increases of muscarinic receptor binding after cochlear ablation might reflect new expression of muscarinic receptors and might result from sprouting of new fibers, possibly from OCN or from the ventral, trapezoid body, pathway (Bilak et al, 1997;Illing et al, 1997Illing et al, , 2000Kraus and Illing, 2004). Sprouting in some CN regions is supported by our finding of increased ChAT activity after cochlear ablation, but it is not supported in those regions, such as DCN layers, where increases of receptor binding occurred without increases of ChAT activity (Jin et al, 2005).…”
Section: Effects Of Cochlear Ablation On Muscarinic Acetylcholine Recmentioning
confidence: 54%
“…Previous studies have also demonstrated that the MOC can somewhat reduce the temporary threshold shift that occurs as an early manifestation of the damaging effects of loud sounds (guinea pig: Roberston and Johnstone, 1980;Cody, 1992;reviewed in Guinan, 1996), protecting the cochlea from acoustic injury (Taranda et al, 2009). Moreover, after cochlear dysfunction, MOC neurons seem to be a major source of synaptic reorganization in the VC that could possibly entail compensatory activation of the affected ascending auditory pathway (Kraus and Illing, 2004). The functional role of the LOC is still uncertain, but a recent study in mice has shown that lateral olivocochlear feedback maintains the binaural balance in neural excitability required for accurate localization of sounds in space (Darrow et al, 2006).…”
Section: The Olivocochlear Systemmentioning
confidence: 98%
“…This raises the possibility that CHL ultimately has a greater effect on the contralateral AVCN than does CA. After CA, there is a rapid loss of inputs on the side of the ablation, followed by an up-regulation of GAP-43 (Illing et al, 1997;Kraus and Illing, 2004) ipsi ipsi ipsi ipsi ipsi ipsi contra contra contra contra contra contra Fig. 5.…”
Section: Unilateral Hearing Loss Alters Protein Synthesis Bilaterallymentioning
confidence: 99%
“…For example, the regulation of glutamate and glycine release by protein kinase is altered by CA (Zhang et al, 2002(Zhang et al, , 2003a(Zhang et al, ,b, 2004, as are signal transduction pathways (Suneja and Postashner, 2003) and cyclic AMP levels (Mo et al, 2006). CA also can induce the re-emergence of GAP-43 expression in adult animals (Illing et al, 1997;Michler and Illing, 2002;Kraus and Illing, 2004). Each of these findings suggests that CA may have an affect on central auditory system neurons at the gene level (Holt et al, 2005).…”
Section: Introductionmentioning
confidence: 99%